Effects of CLIC4 on Fucoxanthinol-Induced Apoptosis in Human Colorectal Cancer Cells. (10th March 2021) - Yokoyama, Reo; Kojima, Hiroyuki; Takai, Rie; Ohta, Tohru; Maeda, Hayato; Miyashita, Kazuo; Mutoh, Michihiro; Terasaki, Masaru
Abstract: Fucoxanthin is a marine xanthophyll found in edible brown algae, and a metabolite, fucoxanthinol (FxOH), possesses a potent apoptosis inducing effect in many cancer cells. Chloride intracellular channel 4 (CLIC4) is a member of the CLIC family that plays an important role in cancer development and apoptosis. However, the role of CLIC4 in FxOH-induced apoptosis is not well understood. In this study, we investigated whether CLIC4 affects the apoptotic properties of FxOH in human colorectal cancer (CRC) cells under FxOH treatment. Treating human CRC DLD-1 cells with 5.0 μmol/L FxOH significantly induced apoptosis. FxOH downregulated CLIC4, integrin β1, NHERF2 and pSmad2 (Ser 465/467 ) by 0.6-, 0.7-, 0.7-, and 0.5-fold, respectively, compared with control cells without alteration of Rab35 expression. No colocalizing change was observed in CLIC4-related proteins in either control or FxOH-treated cells. CLIC4 knockdown suppressed cell growth and apoptosis. Interestingly, apoptosis induction by FxOH almost disappeared with CLIC4 knockdown. Our findings suggested that CLIC4 could be involved in FxOH-induced apoptosis in human CRC.